Information Security in the System of Ensuring National Security - Shahbazyan, Marine (Տիգրան Մեծ)
As a system-building factor for a modern and dynamically developing society, the information sphere significantly influences the political, economic, cultural, protective, and ideological general state and elements of the states', nations' and individuals' life security, which highlights the importance of information security in the national security system. Information security is a state of national community where the comprehensive and safe protection of a person, society and state is guaranteed from all sorts of information risks and threats, radically oriented political and social forces. Consequently, information security is a complex process to gradually overcome any information risk. The challenges and threats the information security faces determine the specific content of the practical steps and measures that ensure the national security.
Keywords: National Security